Evaluation of COVID-19 protease and HIV inhibitors interactions - Tran Linh (Acta Pharmaceutica, 2022)
The epidemic of the novel coronavirus disease (COVID-19) that started in 2019 has evoked an urgent demand for finding new potential therapeutic agents. In this study, we performed a molecular docking of anti-HIV drugs to refine HIV protease inhibitors and nucleotide analogues to target COVID-19. The evaluation was based on docking scores calculated by AutoDock Vina and top binding poses were analyzed. Our results suggested that lopinavir, darunavir, atazanavir, remdesivir, and tipranavir have the best binding affinity for the 3-chymotrypsin-like protease of COVID-19. The comparison of the binding sites of three drugs, namely, darunavir, atazanavir and remdesivir, showed an overlap region of the protein pocket. Our study showed a strong affinity between lopinavir, darunavir, atazanavir, tipranavir and COVID-19 protease. However, their efficacy should be confirmed by in vitro studies since there are concerns related to interference with their active sites.